Lithium pre-supplementing high-ionic-conductivity lithium battery diaphragm and preparation method thereof

By applying a ceramic coating doped with calcinite-type lithium fluorine-oxygen doped on the lithium battery separator, the problems of low ionic conductivity, poor circulation performance and insufficient high temperature stability of the existing lithium battery separator are solved, and higher conductivity, longer cycle times and better high temperature stability are achieved.

CN119890611AInactive Publication Date: 2025-04-25TIANJIN DG MEMBRANE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411467833.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery separators have low ionic conductivity, poor cycling performance and insufficient high temperature stability, which affect the safety and service life of the battery.

Method used

Pre-compensated lithium high-ion conductivity lithium battery separators are used to form ceramic coatings by doping calcinite-type lithium fluorine-oxygen in traditional ceramic slurry, and coating them on the surface of PP or PE membranes on one or both sides through the online slit extrusion coating technology.

Benefits of technology

It significantly improves the ionic conductivity of the ceramic coated film, enhances the number of cycles and high temperature stability of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890611A_ABST
    Figure CN119890611A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a lithium pre-supplementing high-ionic-conductivity lithium battery diaphragm and a preparation method thereof.The surface of the diaphragm is coated with a ceramic coating, and the ceramic coating comprises, by mass, 12-20 parts of a ceramic material which is aluminum oxide or boehmite; 18 to 40 parts by mass of pyrochlore type lithium oxyfluoride; 0.1 to 0.8 part by mass of a dispersant; 1.4 to 3.2 parts by mass of a binder; 0.1 to 0.2 part by mass of a wetting agent; and 40-60 parts by mass of ultrapure water. The pyrochlore type lithium oxyfluoride is doped in traditional ceramic slurry, the surface of the PP or PE diaphragm is coated with the pyrochlore type lithium oxyfluoride through the technical means in a single-face or double-face mode, the ionic conductivity of a ceramic coating film can be improved, lithium ions in the substance can supplement lithium for a battery, the cycle index of battery charging and discharging is increased, and the service life of the battery is prolonged. And the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium battery separator with high ion conductivity and a preparation method thereof. Background Art

[0002] With the rapid development of society, the environmental and energy crises are becoming increasingly serious. Energy conservation and emission reduction have become a global concern and an inevitable choice for the sustainable development of human society. In order to meet this challenge, all walks of life are constantly undergoing reforms and innovations. Among them, the significant innovation in the automotive industry is the development and application of electric vehicles. As the core component of electric vehicles, the development of battery technology plays a vital role in promoting the progress of this industry.

[0003] However, lithium battery technology has always faced many challenges, especially as the most widely used power battery, the safety and performance of lithium batteries have always been the focus of attention. In the structure of lithium batteries, the diaphragm is a key inner component, which mainly isolates the positive and negative electrodes and prevents short circuits. At the same time, its microporous structure allows lithium ions to pass through to form a charge and discharge loop. However, the lithium battery diaphragms currently on the market have deficiencies in cycle performance, high-speed charge and discharge capabilities, and stability. Especially when charging at room temperature (25°C), thermal expansion is prone to occur, resulting in a decrease in battery performance and affecting its normal use.

[0004] Existing lithium battery separators are usually made of polypropylene (PP) or polyethylene (PE) materials. Such separators have low ionic conductivity, poor cycle rate performance, and insufficient stability of various performances under heat conditions, which affects the overall safety and service life of the battery. These problems have seriously restricted the widespread application of lithium batteries in high-performance electric vehicles. Improving the ionic conductivity of the separator, increasing the number of battery cycles, and enhancing its stability under high temperature conditions have become key requirements for the development of lithium battery technology. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a lithium battery separator with high ion conductivity and a preparation method thereof, which solves the problems of low ion conductivity, poor cycle performance and insufficient high temperature stability of the existing lithium battery separators.

[0006] To achieve the above object, the present invention is implemented by the following technical scheme: a pre-supplemented lithium high ion conductivity lithium battery separator, the surface of the separator is coated with a ceramic coating, and the ceramic coating includes the following components in parts by weight:

[0007] 12-20 parts by mass of a ceramic material, wherein the ceramic material is alumina or boehmite;

[0008] 18-40 parts by mass of pyrochlore-type lithium oxyfluoride;

[0009] 0.1-0.8 parts by mass of a dispersant;

[0010] 1.4-3.2 parts by mass of a binder;

[0011] 0.1-0.2 parts by mass of a wetting agent;

[0012] 40-60 parts by mass of ultrapure water.

[0013] Preferably, the particle size D99 of the ceramic material is less than 2.8 μm.

[0014] Preferably, the pyrochlore-type lithium oxyfluoride has an octahedral polycrystalline microstructure, including lithium, oxygen and fluorine elements, and the pyrochlore-type lithium oxyfluoride can gradually release lithium ions during the use of the battery to replenish the lithium ions in the lithium battery.

[0015] Preferably, the thickness of the ceramic coating is 3.0-3.5 μm.

[0016] Preferably, the ceramic coating is coated on one or both sides of the PP or PE separator by online slot extrusion coating technology.

[0017] The present invention also provides a method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, comprising the following steps:

[0018] S1, adding alumina or boehmite ceramic material, pyrochlore-type lithium oxyfluoride and a dispersant into ultrapure water, stirring and dispersing to obtain a semi-finished product slurry;

[0019] S2, introducing the semi-finished product slurry into a vacuum mixer, adding a binder and a wetting agent, and stirring;

[0020] S3. Ultrasonic treatment is performed on the uniformly stirred slurry, and vacuum is drawn to eliminate bubbles in the slurry to obtain a finished slurry.

[0021] Preferably, in step S1, the stirring and dispersing is carried out in a double planetary mixer at a stirring speed of 30-90 r / min and a dispersing speed of 2000-3000 r / min for 30-60 minutes.

[0022] Preferably, in step S2, the stirring speed of the vacuum stirring is 30-35 r / min.

[0023] Preferably, in step S3, the ultrasonic frequency of the ultrasonic treatment is 5-8 kHz, the vacuum treatment is performed at a vacuum degree of -0.8 MPa or above, and the treatment time is 15-30 minutes.

[0024] Preferably, the finished slurry is coated on a PP or PE diaphragm by an online slot extrusion coating technique and dried at 60-85° C. for 2-4 minutes.

[0025] The invention provides a lithium battery separator with high ion conductivity and a preparation method thereof.

[0026] It has the following beneficial effects:

[0027] 1. The present invention can improve the ionic conductivity of the ceramic coating film by doping pyrochlore-type lithium fluoride oxide into the traditional ceramic slurry and coating it on the surface of PP or PE diaphragm on one side or both sides through technical means. The lithium ions in the substance can replenish lithium for the battery, increase the number of battery charge and discharge cycles, and thus improve the service life of the battery.

[0028] 2. The present invention can effectively improve the ionic conductivity of the battery by coating a ceramic coating on the surface of the PP or PE diaphragm, and replenish the gradually consumed lithium ions during the later use of the battery, thereby increasing the number of battery cycles and extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the attenuation curve of the battery capacity according to the charge and discharge times of the present invention;

[0030] Figure 2 This is a schematic diagram of the microstructure of a conventional aluminum oxide coating of Comparative Example 1 of the present invention, magnified 5K times;

[0031] Figure 3 This is a schematic diagram of the microstructure of a conventional boehmite coating of Comparative Example 2 of the present invention, magnified 5K times;

[0032] Figure 4 This is a schematic diagram of the microstructure of a ceramic coating formed by adding alumina to pyrochlore-type lithium oxyfluoride in Example 2 of the present invention, magnified 5K times;

[0033] Figure 5 This is a schematic diagram of the microstructure of a ceramic coating formed by boehmite doped with pyrochlore-type lithium oxyfluoride in Example 3 of the present invention, magnified 5K times. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0037] 1. Material ratio: Take 18 parts by mass of aluminum oxide and 18 parts by mass of pyrochlore-type lithium oxyfluoride, add them to 55 parts by mass of ultrapure water, and add 0.52 parts by mass of a dispersant.

[0038] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0039] 3. Addition of binder and stirring: introduce the evenly dispersed semi-finished product slurry into a vacuum mixer, add 1.55 parts by mass of binder and 0.13 parts by mass of wetting agent, and continue stirring at a stirring speed of 32 r / min.

[0040] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0041] 5. Coating and drying: The finished product slurry is coated on one side of the 9.0 μm thick PE diaphragm surface using online slot extrusion coating technology, and the coating thickness is 3.2 μm. The coated ceramic layer is dried at 63°C for 3 minutes. The line speed of the coating machine is 42 m / min.

[0042] Embodiment 2:

[0043] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0044] 1. Material ratio: Take 18 parts by mass of aluminum oxide and 36 parts by mass of pyrochlore-type lithium oxyfluoride, add them to 58 parts by mass of ultrapure water, and add 0.55 parts by mass of a dispersant.

[0045] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0046] 3. Addition of binder and stirring: introduce the evenly dispersed semi-finished product slurry into a vacuum mixer, add 1.55 parts by mass of binder and 0.14 parts by mass of wetting agent, and continue stirring at a stirring speed of 35 r / min.

[0047] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0048] 5. Coating and drying: The finished product slurry is coated on one side of the 9.0 μm thick PE diaphragm surface using online slot extrusion coating technology, and the coating thickness formed by coating is 3.2 μm. The coated ceramic layer is dried at 64°C for 3 minutes. The line speed of the coating machine is 44 m / min.

[0049] Embodiment 3:

[0050] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0051] 1. Material ratio: Take 18 parts by mass of boehmite and 18 parts by mass of pyrochlore-type lithium oxyfluoride, add them to 55 parts by mass of ultrapure water, and add 0.52 parts by mass of a dispersant.

[0052] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0053] 3. Addition of binder and stirring: The evenly dispersed semi-finished product slurry was introduced into a vacuum mixer, 1.63 parts by mass of binder and 0.14 parts by mass of wetting agent were added, and stirring was continued at a stirring speed of 35 r / min.

[0054] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0055] 5. Coating and drying: The finished product slurry is coated on one side of the 9.0 μm thick PE diaphragm surface using online slot extrusion coating technology, and the coating thickness formed by coating is 3.14 μm. The coated ceramic layer is dried at 60°C for 3 minutes. The line speed of the coating machine is 40 m / min.

[0056] Embodiment 4:

[0057] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0058] 1. Material ratio: Take 12 parts by mass of aluminum oxide and 16 parts by mass of pyrochlore-type lithium oxyfluoride, add them to 45 parts by mass of ultrapure water, and add 0.33 parts by mass of a dispersant.

[0059] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0060] 3. Addition of binder and stirring: introduce the evenly dispersed semi-finished product slurry into a vacuum mixer, add 1.25 parts by mass of binder and 0.08 parts by mass of wetting agent, and continue stirring at a stirring speed of 32 r / min.

[0061] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0062] 5. Coating and drying: The finished product slurry is coated on one side of the surface of the 9.0 μm thick PE diaphragm using online slot extrusion coating technology, and the coating thickness formed by coating is 3.0 μm. The coated ceramic layer is dried at 60°C for 2 minutes. The line speed of the coating machine is 42 m / min.

[0063] Embodiment 5:

[0064] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0065] 1. Material ratio: Take 13 parts by mass of boehmite and 15 parts by mass of pyrochlore-type lithium oxyfluoride, add them to 45 parts by mass of ultrapure water, and add 0.35 parts by mass of a dispersant.

[0066] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0067] 3. Addition of binder and stirring: The evenly dispersed semi-finished product slurry was introduced into a vacuum mixer, 1.31 parts by mass of binder and 0.07 parts by mass of wetting agent were added, and stirring was continued at a stirring speed of 35 r / min.

[0068] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0069] 5. Coating and drying: The above-mentioned finished product slurry is coated on one side of the surface of the 9.0μm thick PE diaphragm using online slot extrusion coating technology, and the coating thickness formed by coating is 3.0μm. The coated ceramic layer is dried at 60℃ for 2 minutes. The line speed of the coating machine is 40m / min.

[0070] Comparative Example 1:

[0071] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0072] 1. Material ratio: Take 18 parts by mass of aluminum oxide, add it to 55 parts by mass of ultrapure water, and add 0.52 parts by mass of dispersant.

[0073] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 42 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0074] 3. Addition of binder and stirring: introduce the evenly dispersed semi-finished product slurry into a vacuum mixer, add 1.55 parts by mass of binder and 0.13 parts by mass of wetting agent, and continue stirring at a stirring speed of 32 r / min.

[0075] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0076] 5. Coating and drying: The finished product slurry is coated on one side of the 9.0 μm thick PE diaphragm surface using online slot extrusion coating technology, and the coating thickness is 3.2 μm. The coated ceramic layer is dried at 63°C for 3 minutes. The line speed of the coating machine is 42 m / min.

[0077] Comparative Example 2:

[0078] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0079] 1. Material ratio: Take 18 parts by mass of boehmite, add it to 55 parts by mass of ultrapure water, and add 0.52 parts by mass of dispersant.

[0080] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0081] 3. Addition of binder and stirring: The evenly dispersed semi-finished product slurry was introduced into a vacuum mixer, 1.63 parts by mass of binder and 0.14 parts by mass of wetting agent were added, and stirring was continued at a stirring speed of 35 r / min.

[0082] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0083] 5. Coating and drying: The finished product slurry is coated on one side of the 9.0 μm thick PE diaphragm surface using online slot extrusion coating technology, and the coating thickness formed by coating is 3.14 μm. The coated ceramic layer is dried at 60°C for 3 minutes. The line speed of the coating machine is 40 m / min.

[0084] Comparative Example 3:

[0085] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0086] 1. Material ratio: Take 12 parts by mass of aluminum oxide, add it to 45 parts by mass of ultrapure water, and add 0.33 parts by mass of dispersant.

[0087] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0088] 3. Addition of binder and stirring: introduce the evenly dispersed semi-finished product slurry into a vacuum mixer, add 1.25 parts by mass of binder and 0.08 parts by mass of wetting agent, and continue stirring at a stirring speed of 32 r / min.

[0089] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0090] 5. Coating and drying: The finished product slurry is coated on one side of the surface of the 9.0 μm thick PE diaphragm using online slot extrusion coating technology, and the coating thickness formed by coating is 3.0 μm. The coated ceramic layer is dried at 60°C for 2 minutes. The line speed of the coating machine is 42 m / min.

[0091] Comparative Example 4:

[0092] A method for preparing a lithium battery separator with high ion conductivity and pre-supplemented lithium, the specific steps are as follows:

[0093] 1. Material ratio: Take 13 parts by mass of boehmite, add it to 45 parts by mass of ultrapure water, and add 0.35 parts by mass of dispersant.

[0094] 2. Dispersion step: Place the above mixture in a double planetary mixer and stir for 30 minutes at a stirring speed of 40 r / min and a dispersion speed of 2000 r / min to obtain a uniform semi-finished product slurry.

[0095] 3. Addition of binder and stirring: The evenly dispersed semi-finished product slurry was introduced into a vacuum mixer, 1.31 parts by mass of binder and 0.07 parts by mass of wetting agent were added, and stirring was continued at a stirring speed of 35 r / min.

[0096] 4. Ultrasonication and vacuuming: The uniformly stirred slurry is subjected to ultrasonic treatment at an ultrasonic frequency of 6kHz. At the same time, vacuuming is performed at a vacuum degree of more than -0.8MPa. The ultrasonication and vacuuming time are both 15 minutes to eliminate hidden bubbles in the slurry and obtain the finished slurry.

[0097] 5. Coating and drying: The above-mentioned finished product slurry is coated on one side of the surface of the 9.0μm thick PE diaphragm using online slot extrusion coating technology, and the coating thickness formed by coating is 3.0μm. The coated ceramic layer is dried at 60℃ for 2 minutes. The line speed of the coating machine is 40m / min.

[0098] Test experiment:

[0099] Objective: To verify the performance differences between lithium battery separators using pyrochlore-type lithium oxyfluoride reinforced ceramic coatings and traditional ceramic coating separators, including ionic conductivity, battery internal resistance, thermal shrinkage, and battery charge and discharge cycle performance.

[0100] Experimental Materials:

[0101] Example 1-5: Ceramic coating separator using pyrochlore type lithium oxyfluoride.

[0102] Comparative Examples 1-4: Conventional alumina and boehmite ceramic coated diaphragms.

[0103] Experimental equipment:

[0104] Battery testing system: used to test the number of charge and discharge cycles and internal resistance of the battery.

[0105] Microstructure Analyzer: used to analyze the microstructure of the diaphragm.

[0106] Thermal Shrinkage Tester: used to test the dimensional stability of the diaphragm at high temperatures.

[0107] Tensile testing machine: used to determine the mechanical strength of the diaphragm.

[0108] Experimental procedures

[0109] 1. Material preparation:

[0110] The coating slurries were prepared according to the formulations in Examples and Comparative Examples.

[0111] The slurry is coated on the PE or PP base film by online slot extrusion coating technology to form a separator.

[0112] The coated diaphragm is dried at a specified temperature to obtain the final product.

[0113] 2. Diaphragm performance test:

[0114] Measure the thickness, surface density, air permeability, tensile strength, elongation, breakdown voltage, thermal shrinkage and ionic conductivity of the separator.

[0115] The battery is assembled using a battery testing system and subjected to charge and discharge cycle testing (the battery maintains no less than 80% of its capacity).

[0116] 3. Data recording and analysis:

[0117] Record all experimental data, including the results of mechanical properties tests, electrochemical performance tests, and thermal stability tests.

[0118] The test results are shown in Table 1 and Table 2:

[0119] Table 1 Diaphragm characteristics test results

[0120]

[0121]

[0122]

[0123] Note: MD stands for longitudinal direction of the diaphragm, and TD stands for transverse direction of the diaphragm.

[0124] Table 2 Battery charge and discharge cycle times

[0125]

[0126] It can be concluded from the test data shown in Table 1 that the ionic conductivity of the coating membrane formed by coating the surface of the PE base film with the lithium battery slurry of the present invention (Examples 1-5) is above 7mS / cm, while the ionic conductivity of the membrane coated with ceramic slurry alone (Comparative Examples 1-4) is less than 2mS / cm; the ionic conductivity of the battery diaphragm prepared by the present invention is about 4 times that of the ordinary diaphragm. The 130℃*1h shrinkage rate of the coating film of the present invention is within 1.5%, while the 130℃*1h shrinkage rate of the coating film prepared using ceramic materials is greater than 2.2%, which is significantly better than the ceramic coating film. Using the coating film of the present invention, the internal resistance of the battery is within 4.6mΩ, while the internal resistance of the battery of the ceramic coating film is greater than 8.7mΩ.

[0127] From the test results in Table 2, it can be concluded that after 2200 charge and discharge cycles, the battery of the present invention can still maintain no less than 80% of the initial capacity, while the battery prepared using the ordinary ceramic coating film can only be charged and discharged for 1500 cycles. The attenuation curve of the battery capacity with the number of charge and discharge times is shown in Figure 1 shown.

[0128] The lithium ions contained in the new material pyrochlore-type lithium fluoride oxide used in the present invention can replenish lithium to the battery when the battery is charged and discharged, thereby increasing the number of charge and discharge cycles of the battery and thus improving the service life of the battery.

[0129] Microstructure Analysis:

[0130] Figure 2-Figure 5 The microstructures of different coating materials are shown at 5,000 times magnification. These images intuitively show the uniformity of the material structure, particle distribution, and pore characteristics, which directly affect the electrochemical properties and mechanical stability of the battery separator.

[0131] Figure 2 : Microstructure of conventional alumina coating (Comparative Example 1). It can be observed in the image that the distribution of alumina particles is very uneven, the surface is rough, and the particle size and shape are different. There are large gaps between particles and the pore structure is irregular, which may cause lithium ions to encounter greater obstacles when passing through the separator, thereby reducing ionic conductivity and increasing battery internal resistance.

[0132] Figure 3 : Microstructure of conventional boehmite coating (Comparative Example 2). The image shows that the arrangement of boehmite particles is relatively dense and the shape is relatively regular, but there is still some inhomogeneity. The lack of regularity of the pore structure may limit the effective migration of lithium ions, resulting in lower battery performance, especially in terms of ionic conductivity and battery internal resistance.

[0133] Figure 4: The microstructure of the ceramic coating formed by alumina doped with pyrochlore-type lithium oxyfluoride (Example 2). Compared with conventional alumina coatings, this figure shows a more uniform particle distribution and a delicate surface. The pore structure is more uniform, which effectively optimizes the transmission channel of lithium ions, significantly improves the ionic conductivity of the coating, and reduces the internal resistance of the battery.

[0134] Figure 5 : The microstructure of the ceramic coating formed by boehmite doped with pyrochlore-type lithium oxyfluoride (Example 3). The image shows a complex network structure with tight bonding between particles and uniform and reasonably distributed pores. Compared with conventional boehmite coatings, this structure helps to improve the ionic conductivity and thermal stability of the material, thereby improving the charge and discharge cycle performance of the battery.

[0135] These microstructure images show that the addition of pyrochlore-type lithium oxyfluoride significantly improves the microstructure of the ceramic coating, which directly affects the overall performance of the battery. Through comparative analysis of the images, it is proved that the embodiments of the present invention are superior to the coatings of conventional materials in terms of electrochemical performance and thermal stability.

[0136] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A pre-lithium-supplemented high ion conductivity lithium battery separator, characterized in that: The surface of the diaphragm is coated with a ceramic coating, and the ceramic coating comprises the following components in parts by weight: 12-20 parts of a ceramic material, wherein the ceramic material is alumina or boehmite; 18-40 parts of pyrochlore-type lithium oxyfluoride; 0.1-0.8 parts of dispersant; 1.4-3.2 parts of binder; 0.1-0.2 parts of wetting agent; 40-60 parts of ultrapure water.

2. The pre-lithium supplemented high ion conductivity lithium battery separator according to claim 1, characterized in that: The particle size D99 of the ceramic material is less than 2.8 μm.

3. The pre-lithium supplemented high ion conductivity lithium battery separator according to claim 1, characterized in that: The pyrochlore-type lithium fluoride oxide has an octahedral polycrystalline microstructure and includes lithium, oxygen and fluorine elements. The pyrochlore-type lithium fluoride oxide can gradually release lithium ions during the use of the battery to replenish the lithium ions in the lithium battery.

4. The pre-lithium supplemented high ion conductivity lithium battery separator according to claim 1, characterized in that: The thickness of the ceramic coating is 3.0-3.5 μm.

5. The pre-lithium supplemented high ion conductivity lithium battery separator according to claim 1, characterized in that: The ceramic coating is coated on one side or both sides of the PP or PE separator by online slot extrusion coating technology.

6. A method for preparing a pre-lithium-supplemented high-ion conductivity lithium battery separator, used for preparing the pre-lithium-supplemented high-ion conductivity lithium battery separator as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, adding alumina or boehmite ceramic material, pyrochlore-type lithium oxyfluoride and a dispersant into ultrapure water, stirring and dispersing to obtain a semi-finished product slurry; S2, introducing the semi-finished product slurry into a vacuum mixer, adding a binder and a wetting agent, and stirring; S3. Ultrasonic treatment is performed on the uniformly stirred slurry, and vacuum is drawn to eliminate bubbles in the slurry to obtain a finished slurry.

7. The preparation method according to claim 6, characterized in that: In the step S1, the stirring and dispersing is carried out in a double planetary mixer at a stirring speed of 30-90 r / min and a dispersing speed of 2000-3000 r / min for 30-60 minutes.

8. The preparation method according to claim 6, characterized in that: In step S2, the stirring speed of the vacuum stirring is 30-35 r / min.

9. The preparation method according to claim 6, characterized in that: In step S3, the ultrasonic frequency of the ultrasonic treatment is 5-8 kHz, the vacuum treatment is performed at a vacuum degree of -0.8 MPa or higher, and the treatment time is 15-30 minutes.

10. The preparation method according to claim 6, characterized in that: The finished slurry is coated on a PP or PE diaphragm by an online slot extrusion coating technique and dried at 60-85° C. for 2-4 minutes.

Citation Information

Patent Citations

  • Composite ceramic membrane for lithium ion battery

    CN106711380A

  • Paint for functional coating of high-ionic-conductivity diaphragm as well as preparation method and application of paint

    CN117154344A

  • Electrical separator on the basis of a substrate with ceramic coating

    WO1999057769A1